2011
DOI: 10.1177/1099800411416636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delayed Laboratory Processing on Platelet Serotonin Levels

Abstract: Background Despite the availability of established guidelines for measuring platelet serotonin, these guidelines may be difficult to follow in a hospital setting where time to processing may vary from sample to sample. Purpose The purpose of this study was to evaluate the effect of the time to processing of human blood samples on the stability of the enzyme-linked immunosorbent assay (ELISA) for the determination of platelet serotonin levels in human plasma. Method Human blood samples collected from a conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…Serotonin was stable for one week when stored at +4 °C and at room temperature, provided that the samples had been initially centrifuged within two hours. These results confirm those of previous reports [10,20]. Therefore, serum samples can be handled and transferred at room temperature, which is an advantage for today's centralized clinical laboratories.…”
Section: Analytical Validation Of the Serotonin Assaysupporting
confidence: 91%
“…Serotonin was stable for one week when stored at +4 °C and at room temperature, provided that the samples had been initially centrifuged within two hours. These results confirm those of previous reports [10,20]. Therefore, serum samples can be handled and transferred at room temperature, which is an advantage for today's centralized clinical laboratories.…”
Section: Analytical Validation Of the Serotonin Assaysupporting
confidence: 91%
“…Of the newly discovered factors, the importance and prognostic relevance of depression have been proven in several large, prospective studies. [ 2 3 ] A meta-analysis[ 1 ] by the National Institutes of Health reported that, among patients with coronary disease, approximately 20% had been diagnosed with major depression and 47% suffered from depression at the time of the study. In addition, it has been reported that the depression morbidity of patients who have sustained MI is as high as 20%,[ 4 ] and that, in patients with stable CHD, the relationship between depression and cardiac mortality may last for more than 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] The precise mechanism accounting for the association remains unknown, but an important role of 5-HT has been proposed: excessive 5-HT in depression may increase platelet activity and trigger platelet aggregation, which may trigger the plaque formation associated with CHD. [ 2 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has indicated that serotonin in blood is located almost exclusively in platelets (24 ). Therefore, blood processing steps that change platelet metabolism, induce platelet activation, or strive for platelet separation from plasma (platelet-rich plasma vs platelet-poor-plasma) would also be critical for reproducible serotonin analysis from blood (25 ).…”
Section: Metabolomementioning
confidence: 99%